The influence of insignia on store environment - Marques, S.; Salgueiro, M. de F. (36th EMAC Conference, 2007)
In order to analyse store choice criteria, it is required to consider the environment of the store (Baker et al., 2002). The ambient, the design of the store and the personal service are the factors under analysis since they are considered the most relevant ones (Baker et al., 1992). This paper uses Confirmatory Factor Analysis (CFA) to test a store environment measurement model (16 hypermarkets in the Lisbon Metropolitan Area). A multiple group CFA is used to study the influence of the insignia on store environment. Section two describes the theoretical model under analysis. Section three fits a measurement model using CFA. Section four investigates the influence of insignia on store environment and section five discusses the contributions and implications of the study.